(untitled) (Fiep Bulletin - online, 2015)
The present work consists of a study of case with a carrying adolescent of Rett syndrome, where we look for to point out the proposal of physical activity in such a way searching an improvement of the quality of life for this individual in motor and psycho-social aspects, for this work we use activity in the water (hydrotherapy) and activities of psiychomotricity. To judge if individual had improvements in the life of this was made a daily one of field, and we always used the depositions of the mother also to give emphasis to our work. We had resulted of evolution of this individuo how much the motor, cognitive aspects and affective such as; of improvement in the balance; improvement of the object footprint; an improvement of the concentration of individuo in the accomplishment of the activities proposals; a bigger confidence of individuo in accomplishment of the activities, a significant improvement of mood.